Pengaruh Modal Kerja Terhadap Pendapatan Pedagang Pasar Baru Karawang - Anggita Larasati; Uus MD Fadli (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The welfare of a trader can be measured from his income, therefore the factors that influence traders' income must be taken into account so that traders' income is stable and their welfare increases so that buying and selling activities in the market continue to run smoothly, the number of existing traders will remain and increase. In starting a trading business, one of the most important things needed is capital. so it will increase income. The higher the capital used, the higher the income. Vice versa, the lower the capital used, the lower the income earned will be. This research aims to determine the effect of working capital on the income of traders in the Karawang Baru market. This research method used is a quantitative research method. In processing the data, we used the SPSS application to analyze the independent influence variables and dependent variables. The results of this research show that working capital influences the income of Pasar Baru Karang traders. This is shown from the analysis of simple linear regression results which obtained significant values. This means that working capital influences the income of traders at Pasar Baru Karawang. Because most traders obtain capital through loans. So traders are motivated to maximize profits so they can repay the loan.